[Rezension von: Slavery and dependence in ancient Egypt] - Moreno García, Juan Carlos (JAOS, 2025)
Slavery and Dependence in Ancient Egypt: Sources in Translation. Edited by Jane L. Rowlandson, Roger S. Bagnall, and Dorothy J. Thompson. Cambridge Universtiy Press, 2024. Pp. xl + 485, illus. $49.99 (paper).